Novelties in Malagasy Euphorbia (Euphorbiaceae) - Haevermans, Thomas; Hetterscheid, Wilbert L. A. (Phytotaxa, 2021)
In this paper we clarify the identity and natural distribution of Euphorbia milii by defining an epitype for it, and elevate to specific rank infraspecific names published under E. milii and provide detailed synonymy for taxa reinstated at the specific rank such as Euphorbia splendens, Euphorbia bevilaniensis, Euphorbia hislopii. We publish novelties such as E. cylindroclada, Euphorbia imperatae (including Euphorbia milii forma lutea), Euphorbia pachyspina, Euphorbia tananarivae, and Euphorbia werneri.We also investigate the taxonomy and nomenclature of other Malagasy succulent Euphorbia and identify new synonyms for Euphorbia beharensis, Euphorbia berevoensis, Euphorbia delphinensis, Euphorbia mangokyensis, Euphorbia paulianii, and Euphorbia bosseri. We publish at a new rank E. begardii (basionym E. primulifolia var. begardii), E. crassicaulis (basionym E. francoisii var. crassicaulis, with a new synonym E. decaryi var. crassicaulis), and Euphorbia hardyi (basionym E. platyclada var. hardyi). We also clarify the typification of E. isalensis. lectotypify Euphorbia leandriana and, clarify its circumscription, with E. horombensis as a new synonym of this name.